2015
DOI: 10.1016/j.jand.2014.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Black Tea Intake on Blood Cholesterol Concentrations in Individuals with Mild Hypercholesterolemia: A Diet-Controlled Randomized Trial

Abstract: Habitual intake of black tea has been associated with relatively lower serum cholesterol concentrations in observational studies. However, clinical trial results evaluating the effects of black tea on serum cholesterol have been inconsistent. Several factors could explain these mixed results, in particular, uncontrolled confounding caused by lifestyle factors, e.g. diet. This diet-controlled clinical trial estimates the effect of black tea flavonoid consumption on cholesterol concentrations in 57 borderline hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 52 publications
(58 reference statements)
1
20
0
6
Order By: Relevance
“…Similar results were observed in some12, 31 but not all previous studies 30, 32. Total/HDL cholesterol reflects the balance between the cholesterol carried by atherogenic and protective lipoproteins 33.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results were observed in some12, 31 but not all previous studies 30, 32. Total/HDL cholesterol reflects the balance between the cholesterol carried by atherogenic and protective lipoproteins 33.…”
Section: Discussionsupporting
confidence: 88%
“…In one of these clinical trials, the effective dose was 2.5 g black tea and phytosterol mixture which contains 1 g plant sterols for 4 weeks [51]. However, for the other study, a specific dose is not specific, but five cups of black tea per day for two 4-week treatment periods [52]. On the other hand, the consumption of "Benifuuki" green tea, which is rich in methylated catechins (3 g of green tea extract/three times daily for 12 weeks) contributed significantly to reduce serum total cholesterol and serum LDL cholesterol compared to "Yabukita" green tea or barley infusion (placebo tea) consumers [53].…”
Section: Camellia Sinensis and Hypercholesterolemiamentioning
confidence: 99%
“…Eight RCTs examined the effects of tea interventions on cholesterol levels, lipid profile and distribution [6,[39][40][41][42][43][44]. In most studies 3 to 5 cups of tea were ingested daily [6,41,42,44]. One trial comprised of two 2-week treatment periods found that amongst borderline hypercholesterolemic subjects 5 cups of tea daily did not alter lipid profiles [42].…”
Section: Sone Et Al [51]mentioning
confidence: 99%
“…In most studies 3 to 5 cups of tea were ingested daily [6,41,42,44]. One trial comprised of two 2-week treatment periods found that amongst borderline hypercholesterolemic subjects 5 cups of tea daily did not alter lipid profiles [42]. A longer 12-week trial providing 3 cups (each 200 ml) of black tea infusate to normal healthy adults showed that triglyceride levels reduced by 35.8%, and LDL/HDL plasma cholesterol ratio reduced by 16.6% [44].…”
Section: Sone Et Al [51]mentioning
confidence: 99%